Burnout y su relación con el bienestar psicológico de los docentes del instituto técnico agrícola de Salazar (2020)
The present study had the general objective of determining the Relationship of Burnout syndrome in the psychological well-being of the teachers of the Salazar Agricultural Technical Institute and its impact on job performance through psychological tests; using for it the theory of Psychological Well-being of Riff. The type of research is quantitative with descriptive design, the sample was represented by 22 participants. According to the results obtained, it could be concluded that if there is a significant incidence of Burnout Syndrome in the psychological well-being of the participants, evidencing the correlation between high emotional exhaustion, high level of depersonalization and low self-realization, as it negatively influenced Mainly in self-knowledge and mastery of the environment related to psychological well-being, which means that these participants are not comfortable in their workplace, and the work performance of teachers at the Technical Institute of Agriculture in Salazar is affected.